Iraqi ports and their role in the maritime transport movement (Umm Qasr Port, reality and future prospects) Case study (Journal of the College of Basic Education, 2023)
The current research aims to reveal the importance of the role of the commercial port in activating and revitalizing the trafficMaritime navigation is taken from the Iraqi port of Umm Qasr as a special case that shows the importance of this effect on the movement ofMaritime transport and its economic return. The research discussed the historical origins of the port concept and its classifications.according to economic activities and their temporal development, and to clarify the most important basic frameworks for its development on which This is in accordance with the external changes of global trade and the different modes of transportation.The research also focused on the status of the Iraqi ports and their current situation in general, and the port of Umm Qasr.